History of investigation and prospects for application of acetone – butyl fermentation: to the 150th anniversary of the birth of Ch. Weizmann, scientist, politician, native of Belarus - Puchkova, Tatsiana A.; Lysak, Vladimir V.; Vasylenko, Svetlana L. (Experimental Biology and Biotechnology, 2024)
Ch. Weizmann is a scientist and statesman whose homeland is the territory that currently belongs to the Belarus. He went down in the history of world biotechnology by introducing the process of acetone – butyl fermentation into industrial production. At the beginning of the 20th century, it was the largest biotechnological process, second in volume only to ethanol production. One of the products of acetone – butyl fermentation is butanol, which can serve as an alternative, renewable source of energy. The competitiveness of microbiological production of butanol depends on world oil prices and the improvement of the processes for its production.
Keywords: Ch. Weizmann; acetone – butyl fermentation; butanol